FTY720 Prevents Spatial Memory Impairment in a Rat Model of Chronic Cerebral Hypoperfusion via a SIRT3-Independent Pathway - Zhang, Miao; Hu, Yuan; Zhang, Jiahui; Zhang, Junjian (Frontiers in Aging Neuroscience, 2021)
Vascular dementia (VD) together with Alzheimer's disease (AD) are the most prevalent types of late life dementia. The important pathological process-Chronic cerebral hypoperfusion (CCH) contributes to both AD and VD. Recent years, accumulating evidence indicate that Fingolimod (FTY720) is neuroprotective to acute cerebral ischemic stroke animal model and now on the way for its clinical translation. Much less attention is paid in FTY720's role in chronic cerebral hypoperfusion (CCH)-related brain damage. To investigate whether FTY720 can improve CCH-induced spatial memory loss and its underlying mechanism, two-vessel occlusion (2VO) rats were subjected to intraperitoneal FTY720 injection for consecutive 7 weeks (1mg/kg, i.p) from day 8 post-operation. Spatial memory was tested with Morris Water Maze (MWM), brains of rats were harvested for an assay of molecular, biochemical and pathology tests. We found that FTY720 treatment significantly reduced the escape latency and increased the target quadrant swimming time of 2VO rats in MWM. The improvement of memory performance paralleled to decreased pro-inflammatory cytokine levels and Iba-1 positive cell numbers in the hippocampus of 2VO rats, indicating FTY720's beneficial effect in mitigating neuroinflammation Furthermore, we found that FTY720 can also alleviate mitochondria dysfunction in 2VO rats as manifested by Malondialdehyde (MDA) reduction and ATP content and ATPase activity upregulation in the hippocampus after treatment. As a master regulator of mitochondria, hippocampal SIRT3 activity reduced in 2VO rats compared with control group. Interestingly, we found no change in hippocampal SIRT3 activity or mitophagy event after FTY720 injection, either. In summary our results show that FTY720 can improve CCH-induced spatial memory loss. The mechanism may involve neuroimmune modification and SIRT3 independent regulation of mitochondrial dysfunction in the hippocampus. This study provides new clues for pathological mechanism of CCHinduced cognitive impairment.